Performance of multiparametric prostate magnetic resonance imaging validated by targeted and systematic transperineal biopsies. Issue 1 (19th August 2022) - Hsi, Richard A.; Dinh, Tru‐Khang; Greer, Matthew; Bensen, Carleen; Mitchell, Marc A.; Li, Amy Y.; Stamm, Andrew; Henne, Manfred
Abstract: Objective: To measure the performance of multiparametric (mp) magnetic resonance imaging (MRI) to identify intraprostatic tumour deposits using a systematic and targeted MR‐guided transperineal prostate biopsy technique. Materials and Methods: Patients underwent a combined systematic and targeted MR‐guided transperineal biopsy procedure in the dorsal lithotomy position under general anaesthesia. Systematic biopsies were spaced 10 mm or less apart and additional biopsies targeted any Prostate Imaging–Reporting and Data System (PI‐RADS) 3, 4 or 5 lesions identified on mpMRI. Cancer detection rates were calculated on a per patient and per lesion basis. Results: A total of 125 patients underwent the biopsy procedure. The positive predictive value (PPV) of mpMRI per patient was 59% for any cancer and 49% for Gleason score (GS) ≥ 7 cancer. The negative predictive value (NPV) of mpMRI per patient was 67% for any cancer and 88% for GS ≥ 7 cancer. On a per lesion basis, the PPV of PI‐RADS 3 lesions for any and GS ≥ 7 cancer was 24% and 10%. For PI‐RADS 4 lesions it was 42% and 32%. For PI‐RADS 5 lesions, it was 76% and 70%. MpMRI failed to identify GS ≥ 7 cancer found on systematic biopsy in 22% of patients. Conclusion: Based on a combination of systematic and targeted transperineal prostate biopsies, mpMRI showed a high NPV and low PPV for GS ≥ 7 cancer on a per patient basis. The PPV of mpMRI on a per lesion basis increased with increasing PI‐RADS score. However, there were a significant number of both false positive as well as false negative (mpMRI invisible) areas within the prostate that contained GS ≥ 7 cancer. Therefore, pathologic confirmation using both targeted and systematic mapping biopsy is necessary to accurately identify all intraprostatic tumour deposits.